The steelband movement : the forging of a national art in Trinidad and Tobago - Stuempfle, Stephen (Barbados : Press University of the West Indies, 1995)
"Tracing the steelband from the Trinidadian tamboo bamboo band, this chronicle begins in the 1930s with young performers of African descent. In the 1940s, civic leaders gave encouragement, and by independence from Britain in 1962, the steelband had become a national symbol. Details the steelband repertoire, ranging from calypsos to favored European selections"--Handbook of Latin American Studies, v. 58.
Includes discography (pages 237-238) , bibliographical references (p. 239-282) and index.
NLJCols20082021
Keywords: Steel bands (Music) -- Trinidad and Tobago -- History; Popular music -- Trinidad and Tobago -- History and criticism; Popular music; Steel bands (Music); Trinidad and Tobago; Culturele antropologie; Steelbands; Nationale identiteit; Criticism, interpretation, etc; History